CALLIGRAPHY LEARNING CONCEPT IN PONDOK PESANTREN MODERN WALI SONGO, PONOROGO DISTRICT, EAST JAVA - Aura Najwa; Rika Ananda Yunisa (Yayasan Haiah Nusratul Islam, 2024)
The art of Islamic calligraphy developed along with the development of Islam brought by the Prophet Muhammad SAW. Until now, calligraphy has grown rapidly and become a popular work of art among the general public to various Islamic institutions. Especially in Islamic boarding schools in various regions, both traditional and modern. Researchers made the Wali Songo modern boarding school as an object of research. The purpose of conducting this research is so that researchers can find out the concept of calligraphy learning at the Wali Songo modern boarding school. Researchers used descriptive qualitative methods in conducting research, using a literature review approach to collect similar data, and conducting interviews with respondents who had a relationship with the Wali Songo modern boarding school. The results obtained from this research are that the Wali Songo modern boarding school uses modern media in the learning process such as blackboards, markers, blackboard rulers, notebooks, reference books, calligraphy special pens, and liquid ink. The students get special guidance from teachers who are competent in the field of calligraphy.